OPTIMIZATION OF PLANNING FOR THE USE OF RAW MATERIALS FOR PRODUCTION OF THE QURAN USING MRP METHOD AT PT. SYGMA EXA GRAPHICS - Deden Nuryana; A Sarmada; Mukhyidin Djaiz (Kreator, 2019)
Optimization is an effort to maximize activities so that they are realized desired or desired advantage. Optimization in form Raw material planning can be defined as an activity which coordinated to achieve certain goals within a certain period of time. Raw material planning has an effect on operating costs, so that errors in inventory will reduce profits. Company Inventory problem, too much supply or even a shortage. Both of these conditions resulted in the emergence of this situation substantial costs. Therefore, it is necessary to plan the raw material inventory with the MRP method to analyze the optimal inventory level.The purpose of planning and planning is to plan and controlling the flow of material into, inside, and out of the factory thus the position of optimal profit which is an attainable goal. Material requirements planning is carried out using the MRP method whose application begins with forecasting the number demand / production for the future. By seeing material requirements planning, then inventory planning is carried out by using the Horizontal Planning method. From the results of Horizontal Planning produce optimal inventory planning.Keywords: optimization, planning, MRP method.